Pengaruh Komunikasi, Pengembangan Karir dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Pemberdayaan Masyarakat dan Desa (DPMD) Kabupaten Alor - Megatren Mokoni (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of Communication, Career Development and Work Discipline on the performance of employees of the Community and Village Empowerment Office of Alor Regency, either partially or simultaneously. Respondents of this study were 43 employees. Collecting data using questionnaires, observation, and literature study. The data is then analyzed using the t-test to determine the partial effect and the F-test to determine the simultaneous effect on performance with the results of the study being:1) The variables of communication, career development, work discipline and employee performance have a Pearson product moment correlation value which is above the limit of 0.3 for the validity test. 2) The variables of communication, career development, work discipline and employee performance have a chronbah alpha value which is above the limit of 0.6 for the reliability test. 3) The variables of communication, career development, work discipline and employee performance have a test value for each classic assumption test which is above alpha and passes the classic assumption test. 4) There is an effect of Communication on Employee Performance in the Community and Village Empowerment Service of Alor Regency, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the research alpha value, which is 5% (0.05) 5) There is an effect of career development on employee performance in the Community and Village Empowerment Service of Alor Regency, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the alpha value of the study, which is 5% (0.05) 6) There is an influence of Work Discipline on Employee Performance in the Empowerment Service Communities and Villages of Alor Regency, as evidenced by the significance value of the t test which is 0.000 which is smaller than the research alpha value of 5% (0.05) 7) There is an influence of Communication, Career Development and Work Discipline on Employee Performance in the Community and Village Empowerment Service of Alor Regency, as evidenced by the significance value of the F test which is 0.000 which is smaller than the research alpha value of 5% (0.05). From the results of the research and the conclusions of the research, the research team suggested to the Respondents (employees of the Alor Regency Community and Village Empowerment Office) that employees are expected to be able to maintain the performance of employees who have been well organized to date, while continuing to improve themselves given the various changes in work situations during the past. pandemic like the one that's happening right now. Suggestions are also given to the Head of the Community and Village Empowerment Service of Alor Regency, so that leaders who have nurtured and built the values ​​of work discipline and organizational culture that have been well ingrained in this scope of work can be maintained and continue to provide enthusiasm, motivation and innovation for the development of employee performance. much better and overall service performance